2023
DOI: 10.3390/molecules28062571
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Properties of Two Schiff-Base Transition Metal Complexes and Their Ligand by Using Multiple Chiroptical Spectroscopic Tools and DFT Calculations

Abstract: Two transition metal complexes were synthesized with Ni(II) and Cu(II) using a tetradentate Schiff-base ligand, (R,R) and (S,S)-N,N′-Bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine. The stereochemical properties of the ligand and the metal complexes were investigated using a combined experimental and theoretical approach. Multiple spectroscopic techniques, which include IR, vibrational circular dichroism (VCD), UV-Vis and electronic circular dichroism (ECD), as well as Raman and the newly discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[ 57 ] to scale the simulated frequencies in the current study. This procedure was applied recently in a study of transition metal complexes [ 58 ] and was shown to facilitate better comparison with the experimental IR and VCD spectra.…”
Section: Methodsmentioning
confidence: 99%
“…[ 57 ] to scale the simulated frequencies in the current study. This procedure was applied recently in a study of transition metal complexes [ 58 ] and was shown to facilitate better comparison with the experimental IR and VCD spectra.…”
Section: Methodsmentioning
confidence: 99%
“…9,20,[22][23][24] One of the most used catalysts in the selective oxidation of prochiral olefins and monoterpenes from citrus fruit wastes, such as R-(+)-limonene, are complexes from the Salen (bis-[salicidene]ethylenediamine) ligand with chiral carbons on the imino bridge located between two aromatic groups. 25,26 These ligands are formed by a condensation reaction of salicylaldehyde (substituted or unsubstituted) with a chiral diamine. The most widely used amine is 1,2-cyclohexanediamine, while the simplest amine is 1,2-ethylendiamine because it is an achiral amine.…”
Section: Introductionmentioning
confidence: 99%